Leadership a critical text - Western, Simon (California SAGE, 2013)
When Simon Western′s Leadership text first published, it received rave reviews from students, academics and practising leaders and managers all over the world. Written in an accessible style, the book challenges the notion of the individual or hero leader. Western develops the idea of leadership as a distributed process and provides a new framework for understanding and implementing this.
Includes bibliographical references (pages 331-348) and index.
Keywords: Leadership